Lessons learnt from horse-related human fatalities: Accident analysis using HFACS-Equestrianism - Meredith Chapman; Kate Fenner; Matthew J.W. Thomas (Heliyon)
Equestrianism has an opportunity to learn lessons relating to safer human-horse interactions from those who no longer have a voice, by drawing data from the investigation of horse-related human fatalities and participating in accident analysis. Many human-horse related injuries and fatalities are not examined in equestrianism for the purpose of developing safer future risk mitigation practice, often due to the philosophy that horse sport is simply dangerous.This study analysed data from the Australian National Coronial Information System (NCIS) relating to fatalities involving human-horse interaction that occurred between 2000 and 2020. A total of 50 human-horse related fatalities were identified from the NCIS database for analysis using a validated accident analysis framework. The aim of the study was to identify what we could learn and potentially do differently to prevent future fatalities. This was done through a detailed frequency analysis of the underlying causes identified from the coronial investigation using Human Factors Analysis and Classification System-Equestrianism (HFACS-Eq), an accident analysis model specifically designed for equestrianism. As to be expected, the analysis found that most fatalities involved falls 56 % (n = 28) resulting in blunt force trauma 96 % (n = 48), with the horse as causal factor 90 % (n = 45).Beyond these obvious findings, the HFACS-Eq analysis revealed additional findings that in turn can guide future health, safety, and welfare advances in equestrianism. The analysis presented in this paper highlights the environment, surroundings, or location in which the human-horse interact as a critical factor of accident causation. Also, the role of non-technical skills such as communication, effective supervision, and adequate leadership were highlighted as factors that could contribute to enhanced safety in this high-risk domain. The human-horse dyad in equestrianism is complex and unique when compared to other high-risk work and non-work activities. A better understanding of the risk factors involved in handling and riding horses, coupled with a model to help mitigate that risk will also set us on the path to a good life for horses because human safety and horse welfare are inextricably linked.